1999
DOI: 10.1111/j.1550-7408.1999.tb04569.x
|View full text |Cite
|
Sign up to set email alerts
|

Polar Tube Proteins of Microsporidia of the Family Encephalitozoonidae

Abstract: Encephalitozoonidae are microsporidia associated with human infections including hepatitis, encephalitis, conjunctivitis, and disseminated disease. Microsporidia produce a small resistant spore containing a polar tube which serves as a unique vehicle of infection. Polar tube proteins (PTPs) from Encephalitozoon hellem. Encephalitozoon (Septata) intestinalis, and Encephalitozoon cuniculi were purified to homogeneity by HPLC. By SDS-PAGE, the Mr of E. hellem PTP was 55 kDa, while the Mr of E. intestinalis and E.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
44
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 14 publications
3
44
0
Order By: Relevance
“…They are ubiquitous in the animal kingdom with over a 1000 species parasitising a wide range of invertebrate and vertebrate hosts, including humans (Wittner and Weiss, 1999). While it had been suggested that the Microsporidia are primitive eukaryotes lacking mitochondria, recent data suggests they are related to the Fungi Keeling, 2003;Thomarat et al, 2004), have homologues for mitochondrial hsp70 (Hirt et al, 1997;Arisue et al, 2002) and a mitochondrial relic organelle (the mitosome) (Williams et al, 2002).…”
Section: Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…They are ubiquitous in the animal kingdom with over a 1000 species parasitising a wide range of invertebrate and vertebrate hosts, including humans (Wittner and Weiss, 1999). While it had been suggested that the Microsporidia are primitive eukaryotes lacking mitochondria, recent data suggests they are related to the Fungi Keeling, 2003;Thomarat et al, 2004), have homologues for mitochondrial hsp70 (Hirt et al, 1997;Arisue et al, 2002) and a mitochondrial relic organelle (the mitosome) (Williams et al, 2002).…”
Section: Overviewmentioning
confidence: 99%
“…Reported prevalence rates in the 25 studies conducted on patients with HIV infection before the widespread use of highly active antiretroviral therapy demonstrated rates that varied between 2 and 70% depending on the symptoms of the population studied and the diagnostic technique employed (Weber and Bryan, 1994;Drobniewski et al, 1995;van Gool et al, 1995;Weitz et al, 1995;Coyle et al, 1996;Deplazes et al, 2000). In immunocompromised patients, Encephalitozoon has been associated with hepatitis, peritonitis, keratoconjunctivitis, sinusitis and disseminated infections involving the lungs and/or kidneys (Zender et al, 1989;Moss et al, 1997;Weber et al, 1997Weber et al, , 1999Wittner and Weiss, 1999;Franzen and Muller, 2001). Three cases of Pleistophora-like microsporidian infection involving skeletal muscles and myositis have been described in two HIV-infected patients and in a non-HIV-infected patient (Chupp et al, 1993;Cali and Takvorian, 2003).…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations